2012
DOI: 10.1016/j.jinorgbio.2012.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The CXXC motifs in the metal binding domains are required for ATP7B to mediate resistance to cisplatin

Abstract: The copper (Cu) exporter ATP7B mediates resistance to cisplatin (cDDP) but details of the mechanism are unknown. We explored the role of the CXXC motifs in the metal binding domains (MBDs) of ATP7B by investigating binding of cDDP to the sixth metal binding domain (MBD6) or a variant in which the CXXC motif was converted to SXXS. Platinum measurement showed that cDDP bound to wild type MBD6 but not to the SXXS variant. Wild type ATP7B rendered ovarian 2008 cells resistant to cDDP. In 2008 and in HEK293T cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…[2] It has been demonstrated that, similarly to Cu, Pt binds to the CXXC motifs of the NMBDs of ATP7B and that such interaction mediates cancer cell resistance to cisplatin. [3,4] Recently, the SSM technique was employed to investigate charge movements (Cu + ) in recombinant human Cu-ATPases. [5][6][7] Addition of ATP to microsomes enriched with recombinant ATP7A/B and adsorbed on a SSM is followed by an electrogenic event recorded as a current transient (see Figure 1 and Supporting Methods).…”
mentioning
confidence: 99%
“…[2] It has been demonstrated that, similarly to Cu, Pt binds to the CXXC motifs of the NMBDs of ATP7B and that such interaction mediates cancer cell resistance to cisplatin. [3,4] Recently, the SSM technique was employed to investigate charge movements (Cu + ) in recombinant human Cu-ATPases. [5][6][7] Addition of ATP to microsomes enriched with recombinant ATP7A/B and adsorbed on a SSM is followed by an electrogenic event recorded as a current transient (see Figure 1 and Supporting Methods).…”
mentioning
confidence: 99%
“…8 mC-LΔ1-5 and mC-LΔ1-6 were constructed by PCR amplification of the first 63 amino acids of ATP7B (1-63) and inserting them into the Xho1 and BamH1 site of pLVX-mCherry upstream of ATP7B-Δ1-5 and ATP7B-Δ1-6 using infusion procedure. Forward and reverse primers used for PCR amplification of the first 63 amino acids were respectively, GGACTCAGATCTCGAGTTATGCCTGAGCAGGAGAGACAG and TAGATCCGGTGGATCCACA TGA CTG GCA AGT CAT GCC.…”
Section: Methodsmentioning
confidence: 99%
“…8 Conversion of the CXXC motif of each MDB to SXXS did not alter subcellular localization of ATP7B but did prevent it from mediating cDDP resistance. Deletion of either the first 5 or all 6 of the MBDs both prevented TGN localization and disabled its ability to mediate resistance.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations